Elites and Parasites - Lidin, Konstantin (project baikal, 2016)
In his late dialogues, Plato defined elites as social groups that produce eidetic images or, in modern parlance, coherent, archetypic and innovative images. Plato embodied the idea of ascetic elites, which restrain personal consumption, in the images of an ideal city with a concentric structure. Hippocrates suggested an idea of a healthy city with well-balanced elements of city and rural ways of life. Open-city elites fulfil their social duty by increasing the flow of the images they produce.
Keywords: elitology; ancient philosophy; ideal cities; urban studies